Pengaruh Kualitas Pelayanan Dan Keputusan Terhadap Loyalitas Pelanggan - Muhammad Mashudi Azrullah (Fakultas Ekonomi Universitas Panca Marga, 2021)
The focus of this research is the influence of service quality and satisfaction on customer loyalty with a case study in “Café : Kofi” Bangil. This research method is quantitative, the subject of this study are customers of “Café : Kofi” Bangil. The sampling technique used was purposive sampling. With a total of 60 respondents. The result show multiple liniear regression test Y + 0,180 + 0,041 + 0,941 + e. shows that the influence of service quality variables is 0,041 an the effect of satisfaction variables is 0,941. Thus the more dominant variable influencing customer loyalty is the satisfaction variable. T-test results indicate that the service quality variable (X1) has no partial effect and is not significant. While the satisfaction variable is partially significant. Test the coefficient of determination R2 obtained 0,899 or 89,9% this means that customer loyalty is influenced by satisfaction variables. Keywords : Quality Of Service, Satisfaction